2011
DOI: 10.3109/17435390.2011.580863
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a physiologicalin vitrosystem to study the transport of nanoparticles through the buccal mucosa

Abstract: A buccal physiological in vitro testing system for the evaluation of the permeability, the transport route and toxic effects of nanoparticles was developed. Carboxyl polystyrene (CP, 20 nm, 200 nm) and amine modified polystyrene (AP, 200 nm) particles were used as reference particles and characterized in biological media. The permeability through excised porcine buccal mucosa was investigated with Franz diffusion cells. To evaluate the transport route, particle uptake into oral H376 cells was recorded and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
38
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 92 publications
(41 citation statements)
references
References 33 publications
1
38
0
2
Order By: Relevance
“…The permeability of 25 nm, 50 nm, and 200 nm PP particles through porcine buccal mucosa was first determined using standardized diffusion cells. Prior to every experiment, the viability and integrity of the used tissue was evaluated 17…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The permeability of 25 nm, 50 nm, and 200 nm PP particles through porcine buccal mucosa was first determined using standardized diffusion cells. Prior to every experiment, the viability and integrity of the used tissue was evaluated 17…”
Section: Resultsmentioning
confidence: 99%
“…Our recent studies demonstrated that negatively charged 20 nm and positively charged 200 nm particles permeated the mucus layer whereas negatively charged 200 nm particles were entrapped within the mucus and formed aggregates 17…”
Section: Introductionmentioning
confidence: 99%
“…Oral porcine mucosa is similar to the human one in ultrastructure and therefore an accepted alternative due to the limited availability of human oral mucosa. 10 Both full-thickness mucosal tissues, masticatory and buccal mucosa (Figure 2A Analyses revealed that the CMS nanocarrier penetrated the masticatory and the buccal mucosa. In the masticatory mucosa, the penetration of most particles was slightly deeper compared to the buccal mucosa but seemed to be limited to the stratum corneum with a penetration depth of 10 μm.…”
Section: The Core-multishell Indocarbocyanine Nanocarrier Penetratementioning
confidence: 96%
“…30 Consequently, tissues were sliced into 5 mm samples after extensively washing them (n = 12). Half of the samples were boiled in water for 1 hour to inactivate the enzymes (zero value).…”
Section: Cell Viabilitymentioning
confidence: 99%